2013
DOI: 10.1073/pnas.1305508110
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of polarized epithelial cells by apical mistrafficking of epiregulin

Abstract: Establishment and maintenance of apico-basolateral trafficking pathways are critical to epithelial homeostasis. Loss of polarity and trafficking fidelity are thought to occur as a consequence of transformation; however, here we report that selective mistrafficking of the epidermal growth factor receptor (EGFR) ligand epiregulin (EREG) from the basolateral to the apical cell surface drives transformation. Normally, EREG is preferentially delivered to the basolateral surface of polarized Madin-Darby canine kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 37 publications
1
39
0
1
Order By: Relevance
“…Previous work from our lab has shown that the basolateral-sorting information of TGFA, AREG and EREG is contained within their respective cytoplasmic domains (Dempsey et al, 2003;Gephart et al, 2011;Singh et al, 2013). The 39-amino-acid cytoplasmic domain of BTC is highly conserved across species (supplementary material Fig.…”
Section: Btc Basolateral-sorting Specificity Resides Within Its Cytopmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work from our lab has shown that the basolateral-sorting information of TGFA, AREG and EREG is contained within their respective cytoplasmic domains (Dempsey et al, 2003;Gephart et al, 2011;Singh et al, 2013). The 39-amino-acid cytoplasmic domain of BTC is highly conserved across species (supplementary material Fig.…”
Section: Btc Basolateral-sorting Specificity Resides Within Its Cytopmentioning
confidence: 99%
“…S1B) (Nakamura et al, 1995;Singh and Coffey, 2014b). Thus, the EExxxL basolateral-sorting motif is the most common basolateral-sorting motif amongst the family of mammalian EGFR ligands; a PxxP motif in EGF, a dileucine motif in TGFA and a YxxΦ motif in EREG are represented only once (Dempsey et al, 2003;Gephart et al, 2011;Groenestege et al, 2007;Singh et al, 2013).…”
Section: Preferential Sorting Of Btc In Polarized Epithelial Cellsmentioning
confidence: 99%
See 3 more Smart Citations